DEVELOPMENT MODEL OF PROFESSIONAL RESPONSIBILITY OF FUTURE SPECIALISTS OF THE ROCKET-AND-SPACE TECHNOLOGY - Kroshka, Nataliia (PSYCHOLOGICAL JOURNAL, 2018)
The author of the article substantiates the need for elaboration and implementation of the model and the program of the telic development of the professional responsibility of future specialists of the rocket-and-space technology. Based on the theoretical foundations of the research, a development model of the professional responsibility of future specialists of the rocket-and-space technology has been built. The model includes psychological conditions of development, thematic blocks and developing measures of the program, psychological structure of the professional responsibility, development criteria of its components. The structural components include: cognitive, motivational-and-affective and action-behavioral. The dynamical aspect of the professional responsibility development, which is embodied in the relationship of all components of the model, has been revealed. In the article there have been considered psychological conditions of development of the professional responsibility of rocket-and-space technology specialists: recognition of responsibility as a professionally significant quality; developing of socially responsible behavior motives; intensity of the volitional qualities of a personality; internality of the subjective control; intensity of a sense of conscience; awareness of the behavior self-regulation in professional activities. The interdependence and the conditionality of these conditions has been demonstrated. The model contains development criteria of the professional responsibility of future specialists of the rocket-and-space technology. The criteria include the following: assimilation of the meaning of the professional responsibility; subjectification of the motives and values of the professional responsible behavior; self-awareness of the professional activities. The program of the development of the professional responsibility of future specialists of the rocket-and-space technology has been presented. The content of the program includes its goal and objectives, methodological framework, specifics of the developing measures by means of the professional- psychological training. Promising directions of further researches concern further elaboration and implementation of the development program of the professional responsibility of future specialists of the rocket-and-space technology; presentation of the approbation results of the elaborated program.